Extraintestinal nematodes of the red fox Vulpes vulpes in north-west Italy. Issue 4 (July 2015) - Magi, M.; Guardone, L.; Prati, M.C.; Mignone, W.; Macchioni, F.
Abstract Extraintestinal nematodes of the red fox (Vulpes vulpes) are a wide group of parasites that infect wild and domestic carnivores and occasionally humans. Nematodes in the cardiopulmonary system, stomach, urinary apparatus and muscle tissue of 165 red foxes (Vulpes vulpes) from north-west Italy (Liguria and Piedmont) were investigated between 2009 and 2012. Of the cardiopulmonary nematodes, a high prevalence of Angiostrongylus vasorum and Eucoleus aerophilus (syn. Capillaria aerophila) was found, 78.2% and 41.8% respectively; Crenosoma vulpis (15.8%) and Filaroides spp. (4.8%) were also found. Spirocerca lupi (23.5%), Aonchotheca putorii (syn. Capillaria putorii) (8.6%) and Physaloptera spp. (2.5%) were detected in the stomach and Pearsonema plica (syn. Capillaria plica) (56.8%) in the bladder. Eucoleus boehmi (syn. Capillaria boehmi) was also detected in the nasal cavities of one of the two foxes examined. A coprological examination revealed eggs of E. aerophilus, A. putorii, S. lupi, Physaloptera spp. and eggs of intestinal parasites. Filarial worms were absent in all the 165 animals examined, nor was there evidence of Trichinella spp. in any of the foxes. The foxes were found to host a high prevalence of many species of extraintestinal nematodes. The prevalence of A. vasorum in foxes found in the present study is among the highest in Europe. In addition, to the best of our knowledge, E. boehmi and Filaroides spp. have never been reported before in this host in Italy.